Effects of commonly used medicinal herbs in Jordan on erythrocyte oxidative stress markers. - Yousif Y. Bilto; Nessrin G. Alabdallat; Ali M. Atoom; Noaman A. Khalaf (GarVal Editorial Ltda., 2021)
Context: Much attention has been given recently to the antioxidant capacity of natural products, with particular interest on those that are frequently consumed by people. Aims: To evaluate the commonly used and frequently consumed edible herbs in Jordan to compare their in vitro and in vivo antioxidant properties. Methods: The in vitro antioxidant properties were tested by pre-incubating washed human erythrocytes with a given herb extract and then exposing these erythrocytes to H2O2 to induce oxidative stress, and then measuring erythrocyte malondialdehyde (MDA) as a marker for lipid peroxidation, protein carbonyl (PC) as a marker for protein oxidation, reduced glutathione (GSH) as a marker for cellular antioxidant status and the percentage of hemolysis as an indicator for the anti-hemolytic activity of the herb. The in vivo antioxidant properties were tested by giving orally aqueous extracts of the herbs tested in vitro to healthy individuals on daily bases for five days, with two blood samples being collected from each individual to measure the above-mentioned markers. Results: Pre-incubation of human erythrocytes in vitro with methanolic extracts of Zingiber officinale, Rosmarinus officinalis, Salvia triloba, Verbena triphylla, Nigella sativa and Origanum syriacum significantly improved erythrocyte MDA, PC and oxidant hemolysis. Oral consumption by healthy individuals of aqueous extracts of the same herbs for 5 days significantly improved erythrocyte MDA, GSH, and superoxide dismutase (SOD) at the sixth day of administration. Conclusions: These results indicate that aqueous extracts of medicinal herbs can be absorbed well and appear in body tissues inflecting in vivo antioxidant properties similar to their in vitro properties.